2007
DOI: 10.1063/1.2821755
|View full text |Cite
|
Sign up to set email alerts
|

High glass-forming ability correlated with fragility of Mg–Cu(Ag)–Gd alloys

Abstract: We report bulk metallic glasses with critical diameter ͑D c ͒ in the 20-27 mm range over a relatively wide composition range in the Mg-Cu-Ag-Gd quaternary system. Such an extraordinary glass-forming ability is correlated with the relatively strong liquid behavior of these alloys in terms of Angell's ͓Science 267, 1924 ͑1995͔͒ fragility concept. The relaxation time of the ternary Mg 61 Cu 28 Gd 11 and quaternary Mg 59.5 Cu 22.9 Ag 6.6 Gd 11 alloys was measured. In terms of the fragility parameter D * , the Mg 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Encouraged by this success, with the effort of scholars all over the world, a number of Ti-based BMGs, such as Ti-Cu-Ni [40,41], Ti-Zr-Be [42,43], Ti-Zr-Cu-Ni-Sn [44,45], Ti-Zr-Cu-Pd-(Sn, Si, Nb) [46][47][48][49][50], Ti-Zr-Cu-Ni-Be [51][52][53], Ti-Zr-Hf-Cu-Ni-Si-Sn [54], and Ti-Cu-Zr-Fe-Sn-Si-(Ag, Sc) [55][56][57], have been developed over the last few decades. Figure 1 shows the maximum diameters for glass formation obtained in different alloy systems and the year in which they were discovered [8,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Compared with other alloy systems (e.g., Zr-, Pd-, Mg-, Fe-, Co-, Ni-, and Cu-based So far, the largest known critical diameter for Ti-based BMGs has been over 50 mm in the Ti-Zr-Cu-Ni-Be [72] and Ti-Zr-Cu-Fe-Be [73] quinary alloy systems.…”
Section: Glass-forming Ability Of Ti-based Bmgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by this success, with the effort of scholars all over the world, a number of Ti-based BMGs, such as Ti-Cu-Ni [40,41], Ti-Zr-Be [42,43], Ti-Zr-Cu-Ni-Sn [44,45], Ti-Zr-Cu-Pd-(Sn, Si, Nb) [46][47][48][49][50], Ti-Zr-Cu-Ni-Be [51][52][53], Ti-Zr-Hf-Cu-Ni-Si-Sn [54], and Ti-Cu-Zr-Fe-Sn-Si-(Ag, Sc) [55][56][57], have been developed over the last few decades. Figure 1 shows the maximum diameters for glass formation obtained in different alloy systems and the year in which they were discovered [8,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Compared with other alloy systems (e.g., Zr-, Pd-, Mg-, Fe-, Co-, Ni-, and Cu-based So far, the largest known critical diameter for Ti-based BMGs has been over 50 mm in the Ti-Zr-Cu-Ni-Be [72] and Ti-Zr-Cu-Fe-Be [73] quinary alloy systems.…”
Section: Glass-forming Ability Of Ti-based Bmgsmentioning
confidence: 99%
“…Maximum diameters of the bulk metallic glass (BMG) rods achieved in different alloy systems and the years in which they were discovered. Data are taken from [8,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
mentioning
confidence: 99%
“…191 The effectiveness in increasing the GFA of alloys by partial replacement of Fe with Co seems to result from the necessity of the long-range atomic rearrangement of the constituent elements required for the simultaneous precipitation of Fe 23 (C,B) 6 and Co 23 (C,B) 6 phases from the supercooled liquid for the Fe-Co-C-B-Tm alloys. It has also been found that the critical diameter increases further to 18 mm by more fine-tuning of the composition of the alloy to (Fe 0?8 Co 0?2 ) 47 192 Considering that the critical diameter of Fe 50 Cr 15 Mo 14 C 15 B 6 is y2 mm, addition of 2-3 at-%Tm is concluded to be very effective in increasing the GFA. Furthermore, the addition of 2%Tm does not cause distinct change in the melting temperature.…”
mentioning
confidence: 99%
“…36 Bulk metallic glasses have also been synthesised in other alloy systems based on Au, 37 Ca, 38 Ce, 39 Hf, 40 Nd, 41 Pr, 42 Sm 43 and Y. 44 Subsequent efforts by different groups also resulted in the development of BMGs with critical diameters of .20 mm in alloy systems based on Cu, 45 Ln, 46 Mg, 47 Ni, 48 Pd, 49 Pt 50 and Zr. 51,52 The general features of BMGs have been described in some reviews and books.…”
mentioning
confidence: 99%
“…As an important branch of the industrial system, metallic glass have been commercialized in several fields such as engineering, medicine, electronics, military, sports, and jewelry making for a period of time [6][7][8][9][10] . A variety of bulk glassy alloys have been developed in lanthanide (Ln)- [11] , Mg- [12] , Zr- [13,14] , Be- [15] , Fe- [16] , Pd-Cu- [17] , Ti- [18] , Ni- [19] , Co- [16] and Cu- [20] based the systems by various slow cooling producing processes such as copper mold casting and water quenching etc. Among these bulk metallic glass systems, Zr-based alloy systems are the most important alloy systems because it conjuncts the achievement of various useful engineering properties with high glass-forming ability.…”
Section: Introductionmentioning
confidence: 99%